Efikasi Diri dan Prestasi Kerja pada Karyawan di PT. X - Lina Yuliana; Konto Iskandar Dinata; Umi Nur Kholifah (Program Studi Tasawuf dan Psikoterapi, 2020)
The research purposed to find the correlation between self-efficacy and job performance on PT. X employee. This research used quantitative method with correlational approach. The sample of this research was 43 people which used total sampling for the technique. The variable of this research were self-efficacy and job performance. The data collection arranged using Likert model scale, self-efficacy scale and job performance scale. Hypothesis tested with product moment correlation technique. The result based on person correlation analyze was positive and significant correlation between self-efficacy and job performance on PT. X employee. The number of pearson correlation between self-efficacy and job performance showed 0,705 with sig. (2-tailed) 0,000 (sig<0,05) means Ha (alternative hypothesis) accepted. The conclusion of the research was positive and significant correlation between self-efficacy and job performance on PT. X employee.